Dipeptides VL increase protein accumulation in C2C12 cells by activating the Akt-mTOR pathway and inhibiting the NF-κB pathway. (February 2022) - Li, Mingliang; Wei, Ying; Feng, Zhiyuan; Cai, Muyi; Xu, Yaguang; Gu, Ruizeng; Ma, Yongqing; Pan, Xingchang
Abstract: The Akt-mTOR signaling pathway plays a central role in regulating intracellular protein metabolism, and the NF-κB signaling pathway plays a vital role in developing skeletal muscle atrophy. In this study, we took the three dipeptides Val-Leu (VL), Leu-Leu (LL), and Leu-Gln (LQ) identified from corn peptides as the research objects and proved that peptides could promote C2C12 cell differentiation and protein synthesis by activating the Akt-mTOR signaling pathway. On the other hand, the dipeptides also inhibited the classical pathway of the NF-κB signaling pathway, down-regulated the expression of two E3 ubiquitin ligases MAFbx and MURF-1, attenuated apoptosis induced by TNF-α, and thus inhibited protein degradation in cells. In conclusion, the dipeptides isolated from corn peptides showed the effect of increasing protein accumulation in skeletal muscle, suggesting the application potential of corn peptides in promoting the growth of skeletal muscle mass. In addition, this experiment compared the different characteristics of the effects of the dipeptide VL and its corresponding amino acid mixture on the Akt-mTOR signaling pathway.